If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + -9x = 12 + -11x Solving 28 + -9x = 12 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. 28 + -9x + 11x = 12 + -11x + 11x Combine like terms: -9x + 11x = 2x 28 + 2x = 12 + -11x + 11x Combine like terms: -11x + 11x = 0 28 + 2x = 12 + 0 28 + 2x = 12 Add '-28' to each side of the equation. 28 + -28 + 2x = 12 + -28 Combine like terms: 28 + -28 = 0 0 + 2x = 12 + -28 2x = 12 + -28 Combine like terms: 12 + -28 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| 14+2x=-8 | | 7x-y=14solvex | | 2(x+7)=-8 | | -26=-364 | | 67-2x=34x+15 | | 14-(x+9)=7x-3 | | 5x+35-6x=1-9x+2 | | 268v*5=345+32v | | 3x+7=123-10x | | 12+x=8 | | 0.5+b+4=2(b+2) | | X+0.5-3=4.5 | | mx^2+(2m-2)x+(m-1)=0 | | .055556*y=-11 | | 40-8x-3x+15=0 | | y/5=-6 | | 15.3=z+29.23 | | 3(x+4)=8 | | 0=-16t^2+100t+10 | | 2x+1=187 | | a+163=292 | | 2(w+1)=3(w-1) | | 2x+(-13y)+(-x)+3y= | | 7x-6+5x-4+3x-2+x=-4 | | -3x-4y=7 | | 4x^2-17x^2+18=0 | | 92+v=92 | | 7-6x+8+4x+3x-4=10+2*3 | | 4x+18=2x+6 | | 7ln(2x)+3=6 | | -4(2x-2)= | | 9x+12-6x-13+2x=8 |